2021
DOI: 10.1038/s41598-020-80567-9
|View full text |Cite
|
Sign up to set email alerts
|

Basiliximab impairs regulatory T cell (TREG) function and could affect the short-term graft acceptance in children with heart transplantation

Abstract: CD25, the alpha chain of the IL-2 receptor, is expressed on activated effector T cells that mediate immune graft damage. Induction immunosuppression is commonly used in solid organ transplantation and can include antibodies blocking CD25. However, regulatory T cells (Tregs) also rely on CD25 for their proliferation, survival, and regulatory function. Therefore, CD25-blockade may compromise Treg protective role against rejection. We analysed in vitro the effect of basiliximab (BXM) on the viability, phenotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Poor CD4 + CD25 + T cell reconstitution increased the risk of infections (51). We observed that patients who recovered from SR-aGVHD after basiliximab treatment had a slower CD4 + CD25 + T-cell recovery compared with event-free HID HSCT recipients, which was supported by previous studies (52,53). Chakupurakal et al (53) observed significant depletion of CD4 + CD25 + T cells in SR-aGVHD patients treated with basiliximab, and Vondran et al (54) reported that basiliximab downregulated the expression of CD25 on T cells in vitro.…”
Section: Discussionsupporting
confidence: 85%
“…Poor CD4 + CD25 + T cell reconstitution increased the risk of infections (51). We observed that patients who recovered from SR-aGVHD after basiliximab treatment had a slower CD4 + CD25 + T-cell recovery compared with event-free HID HSCT recipients, which was supported by previous studies (52,53). Chakupurakal et al (53) observed significant depletion of CD4 + CD25 + T cells in SR-aGVHD patients treated with basiliximab, and Vondran et al (54) reported that basiliximab downregulated the expression of CD25 on T cells in vitro.…”
Section: Discussionsupporting
confidence: 85%
“…Values and functional markers (CD39, CTLA4, Ki67, and HLA-DR) of Foxp3+ Treg cells (CD3+CD4+CD25+Foxp3+) and frequency of Foxp3+ Treg "recent thymic emigrants" (RTE) (CD45RA+CD31+) were also analyzed in PBMCs by intracellular staining as previously described. 12,13 Gating strategies for all these immune populations and subpopulations are shown in Figure 2.…”
Section: Sample Processing and Immune Monitoringmentioning
confidence: 99%
“…Induction agents can affect T cells, including Tregs, at least transiently. Alemtuzumab and thymoglobulin can lead to an increased ratio of Tregs to effector T cells while basiliximab and daclizumab may decrease that ratio 52–56 …”
Section: Discussionmentioning
confidence: 99%
“…Given the small sample size, it was not possible to adjust for daclizumab may decrease that ratio. [52][53][54][55][56] The duration of the impact of induction agents on Tregs is not known, but if it is long lasting, then type of induction may have confounded the relation between sex and Tregs in our study. Even beginning to determine how to quantify adherence as a possible confounder in the relationship between age or sex and immune profile is challenging.…”
Section: (D)mentioning
confidence: 95%